ANTIBACTERIAL ACTIVITY OF SOME PLANT EXTRACTS AGAINST PATHOGENIC BACTERIA ERWINIA CAROTOVORA SUBSP. CAROTOVORA - Bhardwaj, S. K; Laura, J. S. (Potato Journal, 2013)
The aqueous extracts of twenty plants were screened by agar diffusion methods for their antibacterial activity against Erwinia corotovora subsp. carotovora, a causal organism of soft rot of potato. The strongest inhibitory effect was of the leaf extracts of Camellia sinensis, and bark extracts of Acacia arabicae and Acacia catechu. The inhibitory effect against tested bacteria was also shown by leaf extracts of Azadirachta indica, root extracts of Asparagus racemosus, seed extracts of Acacia fernesiana and fruit extracts of Aegle marmelos.